Electromagnetic studies of the western part of the Ukrainian Shield - I. Yu. Nikolaev; A. M. Kushnir; V. A. Ilyenko; Yu. I. Nikolaev (Геофизический журнал, 2019)
Results of synchronous magnetotelluric and magnetovariation researches along profiles Radomyshl—Fastiv and Ruzhin—Skvira conducted in 2015 for studying the deep structure of crust of the western part of the Ukrainian Shield, on purpose of search the zones of metasomatism and the related ore occurrences minerals are given. Tippers for the periods of geomagnetic variations from 20 to 3700 s and curves of apparent resistan-ce from 10 to 10 000 s are received. According to high-quality interpretation of complex tippers and MTZ curves on a profile Radomyshl—Fastiv three local abnormal structu-res are allocated confined to crossing of separate parts of the submeridional faults, such as Vilensky, Kocherivsky and Brusilivsky with the system of sublatitudinal minor faults. The analysis of MTZ curves confirms the non-uniform three-dimensional situation on all the area of research. In the center of Kocherivska sinclinal structure the existence of a high-conductivity zone which roof lies at a depth of 20—50 km is supposed. On a pro-file Ruzhin—Skvira the following anomalies are recognized: the local high-conductivity surface which is situated in the Zvizdal-Zaliska fault zone; the near-surface one which goes deep to the east along the profile and can correspond to the geological structure, namely the Samgorodsky fault of the second order, and it is limited from the west by Ogiyvsky, and from the east by Velikoyerchikivsky deep faults. Anomalies of high electrical conductivity are spatially confined to the known ore-bearing fields — Papirnyanske, Tovstovske and Kocherivske of the rare metal pegmatites and Potashnyanske tungsten ore field. The anomalies allocated spatially coincide with the zones of distribution of metasomatism and metasomatically changed rocks which are promising for endogenic mineralization, namely skarn in the Volynsk megablock; greisens and zones of epi-dotization, quartzitization in Kocherivsky synclinoriums; zones of quartzitization and mik-roklinization of the Zvizdal-Zaliska faults zone; zones of chloritization, mikroklinization, epidotization and hydrothermal change of rocks of the Brusilivska fault zone; zones of a muskovitization, epidotization and quartzitization of the Rosinsky megablock.